Equi-Balancing’ Foreign Policy of The Philippines Toward China: The Implementation Of The Philippines’ Cooperative Maritime Diplomacy To China In The South China Sea Dispute - Jennie Joyce Candice; Anak Agung Banyu Perwita (Jurusan Ilmu Hubungan Internasional, 2021)
This article explicates the implementation of “Equi-Balancing” foreign policy of the Philippines toward China in the South China Sea (SCS) dispute. It argues that in order to protects its core national interests, Philippines should be able to manage its constructive relations with China. In order to do so, Philippines under the Rodrigo Duterte administration formulated and implemented cooperative maritime diplomacy to China. The main objectives of this cooperative maritime diplomacy were creating a closer the Philippines-China relations and on the hand, making some diplomatic distance to the United States in the SCS issue. This article utilises qualitative research method in deciphering the above cooperative maritime diplomacy. To achieve these goals, the Philippines has conducted several concrete actions by building: its sofpower, self confidence and coalition.